TI_GERICHTE 15.2010.56 vom 3. Mai 2010 , Precetto esecutivo. Irricevibilità del ricorso fondato su motivi di merito - TI Tribunale d'appello (2010)
Precetto esecutivo. Irricevibilità del ricorso fondato su motivi di merito